The efficacy of steroids for postoperative persistent inflammatory reaction in a patient with barium peritonitis: A case report. (2017) - Kojima, Hirofumi; Hojo, Shozo; Manabe, Takahiro; Demura, Shiori; Sekine, Shinichi; Shibuya, Kazuto; Hashimoto, Isaya; Yoshioka, Isaku; Okumura, Tomoyuki; Nagata, Takuya; Fujii, Tsutomu
Highlights: Residual barium in intraperitoneal cavity causes persistent inflammatory reaction. Steroids are effective for persistent inflammation caused by residual barium. If infectious or other inflammation origins exist, steroids should be avoided. Abstract: Introduction: Barium peritonitis is a serious and life-threatening disease requiring intensive care. Residual barium in the intraperitoneal cavity can cause persistent inflammation, postoperatively. Presentation of case: An 80-year-old woman was admitted to our hospital because of abdominal pain and vomiting after barium meal examination. Physical and radiographic examination showed sigmoid colon perforation. Barium sulfate extravasation was noted in the intraperitoneal cavity. We diagnosed the patient with barium peritonitis, and performed Hartmann's procedure and thorough lavage of the intraperitoneal cavity with 20-L saline. Postoperative blood examination results were not readily improved because of the residual barium in the intraperitoneal and retroperitoneal cavities. We excluded the presence of any other inflammation origin, except that from residual barium. Methylprednisolone 500 mg/body/day was administered for 3 days and the dose was gradually decreased thereafter. The white blood cell count and serum C-reactive protein levels immediately improved to normal levels. Discussion: Barium peritonitis is associated with high mortality. Residual barium in the intraperitoneal cavity can cause chemical peritonitis, leading to granuloma formation and ileus, postoperatively. Therefore, complete removal of barium in the abdominal cavity with aggressive drainage and large quantity of saline is necessary to prevent postoperative inflammatory reaction. The use of steroids improves the persistent inflammation caused by residual barium, unless any infectious origins are present, which can worsen with steroid-use. Conclusion: Residual barium in the intraperitoneal cavity causes persistent inflammatory reaction in patients with barium peritonitis. The use of steroids is effective for postoperative persistent inflammation due to the residual barium.